Intergenerational Income Mobility in Turkey - Mercan, Murat Anil (Bilgesel Yayincilik San & Tic Ltd, 2012)
This paper aims to calculate intergenerational income mobility in Turkey. We employed two different approaches: a simple OLS and a two-stage model. These three methods produced the same result. We found that the intergenerational income elasticity between fathers and sons is approximately 0.1 in Turkey This result indicates that Turkey is a highly mobile society. This elasticity estimate is lower than those usually reported for the United States. In addition, this elasticity estimate suggests that there is greater mobility in Turkey than in the United States. In addition, this mobility rate is higher than many other countries.
Keywords: Intergenerational mobility; Income; Earnings